Pengaruh Gaya Kepemimpinan Dosen, Metode Belajar, Teknologi Informasi Terhadap Minat Belajar Mahasiswa Pada Universitas di Surabaya - Lewi, Cleavant (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Observing the increasing number of university students in Indonesia who prefer shortcuts namely, cheating to appear successful without possessing the awareness and motivation to study independently and noting that many students experience stress and discomfort with the campus learning environment, leading some to drop out, particularly among students at universities in Surabaya, raises serious concerns. Additionally, the fact that many students outsource part of their assignments to third parties, even being willing to pay a significant amount for the completion of a single task, prompts important questions about the influencing factors that must be addressed promptly. The decline in students' interest in learning such as teaching styles that overly emphasize academic knowledge and lack interactive methods, accompanied by academic pressure or stress in meeting expectations is a common issue in higher education. These factors contribute to student disengagement, boredom, and decreased motivation to learn, ultimately resulting in reduced academic interest. The purpose of this study is to examine the effectiveness of teaching delivered by facilitators and identify the key factors involved in enhancing both the academic performance and deep understanding of each student. Naturally, institutions will need to analyze these findings and implement strategies to improve the quality of learning, especially at universities in Surabaya. This includes focusing on information technology, lecturer leadership styles, and learning methods that align with student interests, in order to produce highly competent graduates who can contribute significantly and meaningfully to Indonesia. This study adopts a quantitative research method, aiming to provide strong empirical evidence, as the data tested is based on numerical and statistical analysis. Through this approach, it can be determined whether lecturer leadership styles, teaching methods, and information technology truly influence students’ learning interest across all study programs at universities in Surabaya.
Keywords: Lecturer's Leadership Style; Learning Methods; Information Technology; Learning Interest; University in Surabaya